Print, publicity, and popular radicalism in the 1790s : the laurel of liberty - Mee, Jon (Cambridge Studies in Romanticism ;, 2016)
Jon Mee explores the popular democratic movement that emerged in the London of the 1790s in response to the French Revolution. Central to the movement's achievement was the creation of an idea of 'the people' brought into being through print and publicity. Radical clubs rose and fell in the face of the hostile attentions of government. They were sustained by a faith in the press as a form of 'print magic,' but confidence in the liberating potential of the printing press was interwoven with hard-headed deliberations over how best to animate and represent the people. Ideas of disinterested rational debate were thrown into the mix with coruscating satire, rousing songs, and republican toasts. Print personality became a vital interface between readers and print exploited by the cast of radicals returned to history in vivid detail by Print, Publicity, and Popular Radicalism. This title will also be available as Open Access.